Two new freshwater crab species from the Eastern Arc Mountains, Tanzania, East Africa (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil; Jonas, Gabrielle I. (Zootaxa, 2024)
This work focuses on two new freshwater crab species from Tanzania, East Africa: Arcopotamonautes parekeeae n. sp. and A. ngae n. sp. The new species are described based on newly identified museum material. Diagnoses, illustrations, and distribution maps are provided for these species, and their conservation status is discussed.